2001
DOI: 10.1159/000049102
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Release Devices for Fluoride Delivery to High-Risk Individuals

Abstract: The latest fluoride research is investigating the use of slow-release devices for the long-term intra-oral provision of fluoride. 174 children aged 8 years with fluoride slow-releasing glass devices were shown to develop 67% fewer new carious teeth and 76% fewer new carious surfaces in a 2-year double-blind caries study. There were 55% fewer new occlusal fissure carious cavities showing that occlusal surfaces were also protected by the fluoride released from the devices. The fluoride devices release low levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
1
20
0
1
Order By: Relevance
“…10 Toumba 11 studied the FSSRD extensively both in vivo and in vitro and concluded that (a) the mean salivary fluoride (F) level with a device containing 13.3% F in human volunteers was elevated to 0.17 ppm compared with 0.01 ppm over a period of one month, 12 (b) the FSSRD posed no risk of F toxicity, since ingesting this device showed no alteration to plasma baseline F levels, 12,13 (c) using an in situ intra-oral model, it was demonstrated that F could exert an equal effect on the remineralisation of enamel slabs on both sides of the oral cavity, indicating that F had distributed to the opposite side of the oral cavity from a single FSSRD, 11 (d) a double blind randomised clinical caries trial, with high caries-risk children showed significantly fewer carious teeth for the F device, than the control (placebo) device group, over a two year period. For dmft-DMFT there were 67% fewer new carious teeth and for dmfs-DMFS there were 76% fewer new carious surfaces, 13,14 and (e) FSSRDs were shown to have very favourable cost-benefit and cost-effectiveness ratios. 15 Since it is presumed that the anti-cariogenic action of F is on the carious lesion, [16][17][18] its movement through and accumulation by plaque biofilms is important.…”
Section: Introductionmentioning
confidence: 95%
“…10 Toumba 11 studied the FSSRD extensively both in vivo and in vitro and concluded that (a) the mean salivary fluoride (F) level with a device containing 13.3% F in human volunteers was elevated to 0.17 ppm compared with 0.01 ppm over a period of one month, 12 (b) the FSSRD posed no risk of F toxicity, since ingesting this device showed no alteration to plasma baseline F levels, 12,13 (c) using an in situ intra-oral model, it was demonstrated that F could exert an equal effect on the remineralisation of enamel slabs on both sides of the oral cavity, indicating that F had distributed to the opposite side of the oral cavity from a single FSSRD, 11 (d) a double blind randomised clinical caries trial, with high caries-risk children showed significantly fewer carious teeth for the F device, than the control (placebo) device group, over a two year period. For dmft-DMFT there were 67% fewer new carious teeth and for dmfs-DMFS there were 76% fewer new carious surfaces, 13,14 and (e) FSSRDs were shown to have very favourable cost-benefit and cost-effectiveness ratios. 15 Since it is presumed that the anti-cariogenic action of F is on the carious lesion, [16][17][18] its movement through and accumulation by plaque biofilms is important.…”
Section: Introductionmentioning
confidence: 95%
“…20,21 Additionally, it has been shown that the use of slow-release devices for fluoride delivery may facilitate rapid remineralization enamel and dentine submitted to acid challenges. 22 However, there are no studies that evaluate the effect of fluoride from glass-ionomer cement restorations on progression of root dentine erosion.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among the factors that have been related to greater cariogenic activity are inadequate dental hygiene and care, the existence of active caries or a family history of caries, a high concentration in the mouth of bacteria with acido philic activity (Streptococcus mutans or Lactobacillus), reduced salivary fl ow, a cariogenic diet or inadequate levels of fluoride in drinking water. 2 Vari ous authors 3 have shown that fl uoride devices release low levels of fl uoride for at least two years and have great poten tial for use in preventing dental caries in high caries risk groups. Antioxidants constitute an impor tant part of our diet and these, together with intracellular antioxidants and those of the enzymatic systems, can prevent various infl ammatory, infec tious or tumoural processes.…”
Section: Introductionmentioning
confidence: 99%